REPRESENTASI FIGUR TERSEMBUNYI DALAM PEMILU 2024: ANALISIS SEMIOTIKA DESAIN SAMPUL MAJALAH TEMPO EDISI “MALU-MAU MENUNDA PEMILU”: REPRESENTATION OF HIDDEN FIGURES IN THE 2024 INDONESIAN ELECTION: SEMIOTIC ANALYSIS OF TEMPO MAGAZINE COVERS “MALU-MAU MENUNDA PEMILU” EDITION - Galih Wisudha Pratama; Drajatno Widi Utomo; Acep Iwan Saidi (Jurnal Seni dan Reka Rancang: Jurnal Ilmiah Magister Desain, 2024)
Representation of Hidden Figures in The 2024 Indonesian Ellection: Semiotic Analysis of Tempo Magazine Cover “Malu-Mau Menunda Pemilu” Edition. Tempo Magazine regularly publishes issues about the 2024 Election in Indonesia. One of them was published in the edition "Malu-Mau Menunda Pemilu" which was published on March 7 2022. This kind of cover design often makes controversy but also has a positive impact for the identity and attraction of Tempo Magazine. Apart from visualizing political figures, the illustration on the cover image of this edition visualizes hidden figures with multiple interpretations. This research aims to determine the construction of signs on the cover design of the Tempo Magazine edition of "Malu-Mau Menunda Pemilu" in representing hidden figures and to interpret the message. This research uses a qualitative approach with Peirce's semiotic analysis method combined with Moriarty and Keith Kenney's theory of recognition and representation. The results of this research show that the sign construction in this edition's cover design consists of non-verbal and verbal signs which complement each other in conveying messages related to the issue of the postponement of the 2024 election and the extension of the presidential term.